Study of Antibacterial Effects of Hydro - alcoholic Extract of 8 Medicinal Herbs Against Vancomycin Resistant Staphylococcus aureus - MB Majnooni; R Abiri; N S Afnanzade; P Malek Khatabi (Institue of Medicinal Plants, ACECR, 2012)
Background: Staphylococcus aureus is one of the leading bacterial species causing infection in human. This species is or becoming resistant to many antibiotics, including vancomycin.   Objective: As vancomycin is one of the antibiotics used as a last resort for the treatment of the infections caused by S. aureus, therefore identification and application of new effective antibacterial compounds is of utmost importance. In this study, the anti VRSA effects of the hydro alcoholic extracts of 8 Iranian medicinal plants including bulb of Allium ascalonicum, Allium sativum, leave of Utica dioica, Falcaria vulgari, Achillea millefolium and Trigonella foenum and seeds of Trigonella foenum and Brassica alba were surveyed.   Methods: The effects were studied using disk diffusion method and the Minimum Inhibitory Concentration was determined using micro dilution broth methods against 15 VRSA strains.   Results: Among the extracts, the most effective was Allium ascalonicum bulb: MIC 50: 128 μg/ml and Achillea millefolium had the least effect: MIC 50: 1000 μg/ml. Conclusion: As VRSA strains are widespread in the world and treatment of the causative infections is becoming a major problem in medicine, these results, especially results of anti VRSA effects of Allium ascalonicum bulb extract, might be very helpful but clinical application of these extracts and identification of the fractions need further study.